A Clinical-Genetic Score to Identify Surgically Resected Colorectal Cancer Patients Benefiting From an Adjuvant Fluoropyrimidine-Based Therapy - De Mattia, Elena; Dreussi, Eva; Montico, Marcella; Gagno, Sara; Zanusso, Chiara; Quartuccio, Luca; De Vita, Salvatore; Guardascione, Michela; Buonadonna, Angela; D’Andrea, Mario; Pella, Nicoletta; Favaretto, Adolfo; et al. (Frontiers in Pharmacology, 2018)
There are clinical challenges related to adjuvant treatment in colorectal cancer (CRC) and novel molecular markers are needed for better risk stratification of patients. Our aim was to integrate our previously reported clinical-genetic prognostic score with new immunogenetic markers of 5-year disease-free survival (DFS) to evaluate the recurrence risk stratification before fluoropyrimidine (FL)-based adjuvant therapy. The study population included a total of 270 stage II-III CRC patients treated with adjuvant FL with (FL+OXA, n=119) or without oxaliplatin (FL, n=151). Patients were genotyped for a panel of 192 tagging polymorphisms in 34 immune-related genes. The IFNG-rs1861494 polymorphism was associated with worse DFS in the FL+OXA (HR=2.14, 95%CI 1.13-4.08; P=0.020, q-value=0.249) and FL (HR=1.97, 95%CI 1.00-3.86; P=0.049) cohorts, according to a dominant model. The integration of IFNG-rs1861494 in our previous clinical genetic multiparametric score of DFS improved the patients’ risk stratification (Log-rank P=0.0026 in the pooled population). These findings could improve the discrimination of patients who would benefit from adjuvant treatment. In addition, the results may help better elucidate the interplay between the immune system and chemotherapeutics and help determine the efficacy of anti-tumor strategies.